2020
DOI: 10.1155/2020/3818051
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characteristics and Clinical Significance of Different Types of Tumor Vessels in Patients with Stages I-IIA of Squamous Cervical Cancer

Abstract: The determination of factors associated with progression of cervical cancer is important, both for a recurrence risk assessment and for determining optimal treatment tactics. Previously, we showed the prognostic value of different types of tumor microvessels (MVs) in gastric and breast cancer. The object of this research was to study the morphology and clinical significance of different tumor microvessels in early cervical cancer. A total of 65 archived paraffin blocks of patients with I-IIA stages of squamous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 71 publications
1
11
0
2
Order By: Relevance
“…It has been suggested that tumor-associated fibroblasts may originate from bone marrow mesenchymal stem cells, hematopoietic stem cells, tumor cells, and endothelial cells (via endothelial-mesenchymal transition) and may contribute not only to the invasion of malignant neoplasms but also to chemoresistance[ 40 ]. Previously, for stage I-IIA squamous cell carcinoma of the cervix, we found that LFFCT in the tumor stroma was significantly more common in patients with nonkeratinizing cancer ( P = 0.008), a low degree of tumor differentiation ( P = 0.05), a depth of tumor invasion greater than 1 cm ( P = 0.007) and a high risk of disease recurrence ( P = 0.004)[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that tumor-associated fibroblasts may originate from bone marrow mesenchymal stem cells, hematopoietic stem cells, tumor cells, and endothelial cells (via endothelial-mesenchymal transition) and may contribute not only to the invasion of malignant neoplasms but also to chemoresistance[ 40 ]. Previously, for stage I-IIA squamous cell carcinoma of the cervix, we found that LFFCT in the tumor stroma was significantly more common in patients with nonkeratinizing cancer ( P = 0.008), a low degree of tumor differentiation ( P = 0.05), a depth of tumor invasion greater than 1 cm ( P = 0.007) and a high risk of disease recurrence ( P = 0.004)[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…We previously established that tumor microvessels have different morphologies and clinical significance[ 15 - 17 ]. In addition, in squamous cell carcinoma of the cervix, we described the phenomenon of fragmentation of the tumor solid component as the presence of separate fibroblast-like cells in the solid component of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cavitary structures of type-1 were renamed structures with partial endothelial linings, and cavitary structures of type-1 were renamed dilated capillaries with weak expression of CD34. In further studies, it was shown that the proposed classification of tumor microvessels can be used for other localizations of malignant neoplasms[ 190 , 191 ].…”
Section: Heterogenicity Of Tumor Microvessels In Gcmentioning
confidence: 99%
“…Как было отмечено, при РШМ нами описаны несколько типов опухолевых микрососудов, различающихся по морфологии и клинической значимости [25].…”
Section: результаты исследования и их обсуждениеunclassified
“…При изучении особенностей ангиогенеза при раке желудка и раке молочной железы была предложена оригинальная классификация опухолевых микрососудов, которые отличались по морфологии и клинической значимости [23,24]. На основании этой классификации, при плоскоклеточном РШМ были выделены следующие типы опухолевых микрососудов: обычные микрососуды, дилятированные капилляры (ДК) c обычной эндотелиальной выстилкой, ДК со слабо выраженной экспрессией CD34, ДК контактного типа, капилляры в солидном компоненте опухоли, атипичные дилятированные капилляры (АДК), структуры с частичной эндотелиальной выстилкой, лимфатические капилляры в лимфоидных и полиморфноклеточных инфильтратах [25]. Целью настоящего исследования явилась количественная оценка разных типов опухолевых микрососудов при различных гистологических подтипах РШМ, отличающихся чувствительностью к лучевой терапии и к химиотерапии.…”
unclassified